If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(6t-54)=t-4
We move all terms to the left:
1/3(6t-54)-(t-4)=0
Domain of the equation: 3(6t-54)!=0We get rid of parentheses
t∈R
1/3(6t-54)-t+4=0
We multiply all the terms by the denominator
-t*3(6t-54)+4*3(6t-54)+1=0
Wy multiply elements
-3t^2(6+12t(6+1=0
| 5m-8=4=31 | | 14–v=6v | | h+9/5=h−1/35 | | -4-5z=15-5z | | 20-x1/4=-45 | | 15x-8=3=25 | | -108=2(-5+7k)= | | (3x2−14x−5)÷(x−5)=0 | | 2.8=x1.5 | | -2=n+1-3 | | x1/4-20=-45 | | 4s-6=2=36 | | 3p-5=19p= | | 2b-4b=-21+11 | | -356g=11-3g | | 8x-12=4x+4x | | 156+f=225 | | 15x-67=53 | | 8g-16=-5g-2 | | -3=x-14/4 | | 9x+46+-3x+116=180 | | 4x+2-3x+2+5x=20.6 | | 8+8r=3+3r | | -9=x-5+2 | | 8x-32x-4)=3(x-6) | | -4x+9=-6x+3 | | X+24+3x=90 | | 63=3-5j | | 30-x/1/4=-45 | | 7x+12=-24 | | -31-5n=7(1+2n) | | 56+4x+16=11x-12 |